Self-Determined Learning Based on Locus of Control in Accounting Ethic and Corporate Governance Course in Disruption Era - Majidah, Dedy Achmad Kurniady, Muhamad Muslih, Aan Komariah (International Journal of Advanced Science and Technology, 2020)
The purpose of this study was to foster learning independence based on the locus of control in facing the disruption era by using a self-determined learning model on the Accounting Ethic and Corporate Governance course. This study used Classroom Action Research (CAR) on 160 students. CAR was carried out in two cycles. Each cycle was carried out in 3 meetings. The CAR stage used was planning-action-observation-reflection. The results of CAR showed students who chose self-determined learning balanced between online and conventional. Results of assignments and final exam for the conventional class were better than online classes. In online and conventional learning, 55% of students completed assignments with paper compared to online tests. Online group students had an internal locus of control of 65%, whereas, in conventional learning group, internal locus of control was 85%. The success rate of SDtL learning for conventional groups was better than in online groups. This is related to the internal locus of control. To succeed in online classes, students must improve internal locus of control.